Key issues to consider in deliberations on a legal trade in rhino horn - Hanks, John, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Africa's rhinos face an insecure future in the continent's designated protected areas with no solutions in sight in the foreseeable future for securing the required substantial increase in funding for adequately equipped and trained staff. The presentation will review the present and proposed option to reduce rhino poaching with particular reference to their realism and sustainability, and the vital importance of community-led solutions to tackling wildlife crime. The advantages and benefits of a legal trade in rhino horn will be summarized, stressing that an essential prerequisite for the trade is to stop the developed world dictating to Africa on how to manage its wildlife.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.